Cone-beam computed tomography in endodontics: from the specific technical considerations of acquisition parameters and interpretation to advanced clinical applications - Néstor Ríos-Osorio; Sara Quijano-Guauque; Sandra Briñez-Rodríguez; Gustavo Velasco-Flechas; Antonieta Muñoz-Solís; Carlos Chávez; Rafael Fernandez-Grisales (Restorative Dentistry & Endodontics, 2024)
The implementation of imaging methods that enable sensitive and specific observation of anatomical structures has been a constant in the evolution of endodontic therapy. Cone-beam computed tomography (CBCT) enables 3-dimensional (3D) spatial anatomical navigation in the 3 volumetric planes (sagittal, coronal and axial) which translates into great accuracy for the identification of endodontic pathologies/conditions. CBCT interpretation consists of 2 main components: (i) the generation of specific tasks of the image and (ii) the subsequent interpretation report. A systematic and reproducible method to review CBCT scans can improve the accuracy of the interpretation process, translating into greater precision in terms of diagnosis and planning of endodontic clinical procedures. MEDLINE (PubMed), Web of Science, Google Scholar, Embase and Scopus were searched from inception to March 2023. This narrative review addresses the theoretical concepts, elements of interpretation and applications of the CBCT scan in endodontics. In addition, the contents and rationale for reporting 3D endodontic imaging are discussed.